RESEARCH TRENDS AND LITERATURE REVIEW OF SCIENCE TECHNOLOGY SOCIETY IN SCIENCE LEARNING - Nawahdani, Ahmad Mansur; Asrial, Asrial; Nazarudin, Nazarudin (EduFisika: Jurnal Pendidikan Fisika, 2025)
This study aims to analyze research trends and developments in the implementation of the Science Technology Society (STS) approach in science education. The study uses bibliometric analysis and systematic review, with data collected from Scopus, Web of Science, and other databases. Tools include VOSviewer for keyword network analysis and the PRISMA method for data selection. The STS approach significantly enhances critical thinking, collaboration, and problem-solving skills. Key topics include digital technology integration and the role of STS during the COVID-19 pandemic. Gaps exist in applying STS across educational levels and its impact on scientific attitudes. This study provides a comprehensive understanding of STS research trends, emphasizing the integration of digital tools in education and identifying unexplored areas. It advances the knowledge by suggesting future research directions to improve STS implementation.